2019
DOI: 10.1164/rccm.201712-2553oc
|View full text |Cite
|
Sign up to set email alerts
|

FHIT, a Novel Modifier Gene in Pulmonary Arterial Hypertension

Abstract: This study highlights the importance of the novel BMPR2 modifier FHIT in PH and the clinical value of the repurposed drug Enzastaurin as a potential novel therapeutic strategy to improve PAH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 85 publications
(99 reference statements)
1
41
1
Order By: Relevance
“…More recently, FHIT was identified as a potentially clinically relevant BMPR2 modifier gene through an siRNA screen of BMPR2 signaling regulatory genes combined with publicly available PAH RNA expression data. Subsequently, the authors showed that pharmaceutical upregulation of FHIT prevented and reversed experimental pulmonary hypertension in a rat model [ 70 ]. Rhodes and colleagues utilized metabolomics to identify circulating metabolites that distinguish PAH cases from healthy controls, to predict outcomes among PAH cases, and to monitor metabolite levels over time to determine whether correction could affect outcomes [ 71 ].…”
Section: Genetics Of Pediatric Pah—current Knowledgementioning
confidence: 99%
“…More recently, FHIT was identified as a potentially clinically relevant BMPR2 modifier gene through an siRNA screen of BMPR2 signaling regulatory genes combined with publicly available PAH RNA expression data. Subsequently, the authors showed that pharmaceutical upregulation of FHIT prevented and reversed experimental pulmonary hypertension in a rat model [ 70 ]. Rhodes and colleagues utilized metabolomics to identify circulating metabolites that distinguish PAH cases from healthy controls, to predict outcomes among PAH cases, and to monitor metabolite levels over time to determine whether correction could affect outcomes [ 71 ].…”
Section: Genetics Of Pediatric Pah—current Knowledgementioning
confidence: 99%
“…Additionally, we are just now beginning to understand the genetic underpinnings of BMPR2 transcriptional regulation. Elucidating BMPR2 potentiating modifier genes such as FHIT can reveal novel pharmacologic therapies [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence for genetic regulation of BMPR2 by “BMPR2 modifier genes”. We have identified fragile histadine triad ( FHIT ) as one such gene, which, when targeted by the drug Enzastaurin, ameliorates PAH in animal models [ 48 ].…”
Section: Mechanisms For Bmpr2 Deficiencymentioning
confidence: 99%
“…As reduced BMPR2 signalling is a known phenomenon even in patients without the mutation, targeting BMPR2 modifier genes might be an effective rescue mechanism. Enzastaurin was shown to rescue the BMPR2 modifier gene, fragile histidine triad ( FHIT ) and reverse animal PH 183 . Ligand traps inhibiting negative BMPR2 regulation are another therapeutic option.…”
Section: Clinical Utility and Therapeutic Implications Of Genetic Tesmentioning
confidence: 99%